HUBUNGAN PENGETAHUAN IBU TENTANG POLA ASUH DENGAN TUMBUH KEMBANG BAYI USIA 1 - 3 TAHUN DI DESA KAYUBULAN KECAMATAN BATUDAA PANTAI KABUPATEN GORONTALO TAHUN 2013 - Andi Akifa Sudirman; Nikartin Pakaya (-, 2021)
Parenting is a factor that is closely associated with the growth and development of children under three years old. Period of children aged 1-3 years (toddlers) is a period when children still need food and nutritional supplies in sufficient quantities and adequate. Malnutrition during this period may interfere with growth and development physically, mentally, socially and intellectually that are settled and continue until the children become mature.The purpose of this study was: to determine relationship between mother’s knowledge about parenting and  growth and development of infants aged 1-3 years in Kayubulan village in 2012. The research methodology taken: the sample was cooperative mothers who had a toddler (ages 1-3 years) in Kayubulan Village, Batudaa Pantai District, Gorontalo Regency, totaling 32 mothers. And sampling technique used was Porposive Sampling, with analysis of statistical test Chi Square (X2). Results: The results of chi square test showed that the value of X2 (11.520) and sig. (0.001) which was smaller than α (0.05). Conclusions: The results of this study showed there was significant relationship mother’s between knowledge about parenting toddlers and  toddlers’ growth and development in Kayubulan village, Batudaa Pantai District, Gorontalo Regency.